The Benefits Analysis of The Issuance Of Sukuk Savings In Road Infrastructure Development In Indonesia - Guswanto Endra Gautama; Gemala Dewi (Jurnal Dinamika Hukum, 2021)
State Sharia Securities which in technical terms are commonly known as state sukuk, are state securities issued based on sharia principles. One form of state sukuk is a Sukuk Savings. Sukuk Savings is managed based on sharia principles, and has been declared sharia compliance by the National Sharia Council - Indonesian Ulema Council. The proceeds from the issuance will be used for investment activities in the form of purchasing rights to the benefits of State Property to and the procurement of projects to be leased to the Government. Rewards come from the profits from the investment activities. How to regulate the issuance of savings sukuk in the development of road infrastructure in Indonesia and how the potential benefits of its application for economic infrastructure development in Indonesia are the main issues to be analyzed in the paper this. This research uses normative legal research methods. Basically, sukuk is one of the breakthrough sources of funding funds made by the government in implementing its commitment to accelerate infrastructure development and as an alternative investment product with sharia principles for the community.Keyword: Financing; Infrastructure Development; Sukuk Savings